Method for producing coated structure, and coated structure
The electric discharge process forms a stable, uniform metal composite film on base materials at lower temperatures, addressing the issues of high-temperature thermal spraying by reducing thermal history and improving heat and reaction resistance.
Patent Information
- Application Number
- JP2023107243
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2025-01-17
AI Technical Summary
Existing methods for forming protective films on base materials require high-temperature thermal spraying and baking, leading to increased thermal history and the need for large calcining furnaces, and result in thick films that may not be uniform.
A method involving an electric discharge process is used to coat a base material with a metal compound-containing substance, forming a stable metal composite film at lower temperatures, reducing thermal history and ensuring uniformity.
The method allows for the formation of a stable, uniform metal composite film at lower temperatures, improving heat and reaction resistance while reducing energy costs and thermal stress on the base material.
Smart Images

Figure 2025006444000003 
Figure 2025006444000001 
Figure 2025006444000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a coated structure, and a coated structure. [Background technology]
[0002] For components that require heat resistance or reactivity resistance (for example, oxidation resistance or chemical resistance), the heat resistance or reactivity resistance can be improved and the life of the component can be extended by forming a protective film of a metal compound or the like on the surface of the base material.
[0003] For example, Patent Document 1 discloses a method for forming a hard carbide layer on a carbon surface layer, in which a substance that undergoes a carbonization reaction is thermally sprayed onto the surface of a carbon substrate to form a thermal sprayed layer, and then a coating layer made of a substance that has a higher melting point than the substance that undergoes a carbonization reaction and a thermal expansion coefficient equal to or lower than the substance that is carbonized is formed on the thermal sprayed layer, and then heated to form a carbide layer on the carbon substrate surface. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 8-208358 Summary of the Invention [Problem to be solved by the invention]
[0005] However, in the method disclosed in Patent Document 1, when the material forming the sprayed layer contains any of Ti, Ta, W, Nb, Cr, Zr, and Mo, it is necessary to heat the material to a temperature higher than the melting point of the material, and the thermal history of the substrate increases due to the formation of the sprayed layer by spraying and the firing at high temperatures. In addition, in the method disclosed in Patent Document 1, a large firing furnace is required for the carbonization reaction. Furthermore, in the method disclosed in Patent Document 1, it is necessary to form a coating layer on the sprayed layer that is at least twice as thick as the sprayed layer, resulting in the formation of a thick film on the substrate.
[0006] In view of the above problems, the present invention provides a method for producing a coated structure, which can form a stable metal composite coating at low temperatures by a discharge method, reduce the thermal history of the substrate, and produce a coated structure having a uniform metal composite coating on the substrate. The present invention also provides a coated structure. [Means for solving the problem]
[0007] The manufacturing method of a coated structure of the present invention, which has been made to solve the above-mentioned problems, is a manufacturing method of a coated structure having a metal composite coating on a substrate, and is characterized by comprising: a step of applying or immersing a metal compound-containing material on the substrate; and a discharge step of using a discharge electrode to repeatedly discharge between the discharge electrode and the substrate on which the metal compound-containing material has been applied or immersed, thereby forming a metal composite coating on the substrate. The method for producing a coated structure of the present invention can form a stable metal composite coating at low temperatures by a discharge method, and can produce a coated structure having a uniform metal composite coating on the substrate while reducing the thermal history of the substrate.
[0008] In the present specification, a "metal composite coating" may be a coating in which a metal element is present in a state of being bonded to other metal elements, metalloid elements, or nonmetallic elements. Also, in the coating, a metal element may be present in a mixed or dispersed state, rather than being bonded to other metal elements, metalloid elements, or nonmetallic elements. Examples of the metal compound include metal carbides, metal oxides, metal nitrides, metal sulfides, and metal hydroxides.
[0009] Here, the coated structure produced by the method for producing a coated structure of the present invention has a metal composite coating on a substrate, and may be, for example, a substrate having a metal composite coating on at least one side (e.g., the surface) of the substrate, or a substrate having a metal composite coating on the entire peripheral surface of the substrate, and further includes a substrate having a metal composite coating on only a portion of one side of the substrate.
[0010] First, in the step of applying or immersing a substrate in a material containing a metal compound in the method for producing a coated structure of the present invention, the substrate is applied with or immersed in a material containing a metal compound.
[0011] The substrate used in the method for producing a coated structure of the present invention is characterized in that it is a metal-based substrate or a carbon-based substrate. The substrate used in the method for producing a coated structure of the present invention may be a metal-based substrate or a carbon-based substrate, which will be described later.
[0012] Examples of the metal substrate include steel, stainless steel, titanium, copper, aluminum, and tungsten.
[0013] The carbon-based substrate may be a substrate made of only carbon, a substrate mainly made of carbon with a carbon content of 50% by mass or more, or a substrate having a multi-layer structure in which the outermost layer is made of only carbon or mainly made of carbon with a carbon content of 50% by mass or more. It is particularly preferable that the carbon-based substrate is a substrate made of only carbon.
[0014] The size and shape of the substrate are not particularly limited as long as they are capable of discharging from the discharge electrode described below, and may be a plate or a cube.Specific examples of the substrate include crucibles, furnace materials, electrodes, fibers, filtration devices, filters, protective tubes, heater tubes, burner nozzles, and fire-resistant jigs.
[0015] The metal compound-containing material used in the method for producing a coated structure of the present invention is characterized by containing a compound of at least one metal element selected from Ti, Nb, Mo, Hf, Ta, W, and Zr. The metal compound-containing material may include a compound of at least one metal element selected from Ti, Nb, Mo, Hf, Ta, W, and Zr. Specifically, peroxo complex metal compounds (e.g., peroxohydroxy acid complex metal compounds, peroxocitrate complex metal compounds, and peroxoammonium complex metal compounds) containing at least one metal element selected from Ti, Nb, Mo, Hf, Ta, W, and Zr, metal hydroxides, hydroxy acid complex metal compounds (e.g., ammonium oxalate complex metal compounds), and polyacids may be mentioned, but are not limited to these compounds. In addition, the metal compound-containing material may contain a metal element, a semimetal element, or a nonmetal element other than at least one metal element selected from Ti, Nb, Mo, Hf, Ta, W, and Zr. For example, Si, B, and P may be mentioned.
[0016] When the metal compound-containing material is a peroxo complex metal compound containing carbon in the ligand, even if the substrate does not contain carbon, the metal element contained in the peroxo complex metal compound reacts with the carbon to form a metal carbide by heating the substrate coated with the peroxo complex metal compound. Also, when the metal compound-containing material is a hydroxy acid complex metal compound, the metal element contained in the hydroxy acid complex metal compound reacts with the carbon to form a metal carbide.
[0017] The weight ratio of the metal compound-containing material is preferably adjusted according to the type of metal element and carbon-based substrate, and is more preferably more than 0 mass% and not more than 40 mass%, further preferably 0.1 mass% to 30 mass%, particularly preferably 0.2 mass% to 30 mass%, and particularly preferably 0.3 mass% to 15 mass%. When the metal compound-containing material contains a plurality of metal elements selected from Ti, Nb, Mo, Hf, Ta, W, and Zr, the total value of the weight ratios is preferably within the above-mentioned numerical range.
[0018] Here, the weight ratio of the metal compound-containing material may be calculated by diluting the metal compound-containing material appropriately with dilute hydrochloric acid as necessary, and measuring the weight fraction in metal equivalent using ICP optical emission spectrometry (AG-5110 manufactured by Agilent Technologies) in accordance with JIS K0116:2014.
[0019] The metal compound-containing material used in the method for producing a coated structure of the present invention may also contain a resin. If the metal compound-containing material contains a resin, the resin is uniformly compatible with the metal compound and acts to adhere to the substrate, thereby improving film-forming properties and adhesion to the substrate. This is preferable.
[0020] Examples of the resin contained in the metal compound-containing material include polyolefin-based compounds and polyvinyl-based compounds.
[0021] Furthermore, the metal compound-containing material used in the method for producing a coated structure of the present invention may be a solution, a sol, or a gel. The metal compound-containing material is one that contains a metal compound, and more specifically, one that is liquefied by applying a shear stress. In other words, the metal compound-containing material may be one that is liquid, sol, gel, or semi-solid under normal conditions and can be applied to a substrate. Furthermore, the gel may have a viscosity of 200 mPa·s or more at 25°C as measured by a rotating cylinder method.
[0022] In addition, the metal compound-containing material used in the method for producing a coated structure of the present invention is preferably a solution, since it can be easily applied to a substrate. Furthermore, it is preferable that the metal compound-containing material used in the method for producing a coated structure of the present invention contains water as a solvent, from the viewpoint of reducing the environmental load.
[0023] The metal compound-containing material used in the method for producing a coated structure of the present invention is characterized in that the maximum light transmittance in the wavelength region of 500 nm to 700 nm is 70% or more. The metal compound-containing material used in the method for producing a coated structure of the present invention is preferably one having a maximum light transmittance of 70% or more in the wavelength region of 500 nm to 700 nm, since the degree of dispersion is high and the uniformity of the liquid components is excellent. The maximum light transmittance of the wavelength region of 500 nm to 700 nm is more preferably 72% or more, even more preferably 74% or more, particularly preferably 76% or more, particularly preferably 78% or more, and even more particularly preferably 80% or more. The light transmittance of the wavelength region of 500 nm to 700 nm may be 80%. Note that, due to measurement errors, etc., the measured value of the light transmittance may exceed 100%, but since the theoretical upper limit is 100%, if the measured value exceeds 100%, it is considered to be 100%.
[0024] Here, the light transmittance in the wavelength region of 500 nm to 700 nm is measured with a spectrophotometer in accordance with the following transmittance measurement conditions for the metal compound-containing material used in the method for producing a coated structure of the present invention.
[0025] =Light transmittance measurement conditions= Measurement equipment: UV-Vis-NIR spectrophotometer UH4150 (manufactured by Hitachi High-Tech Science Corporation) Measurement mode: Wavelength scan Data mode: %T (transparent) Measurement wavelength range: 200nm~2000nm Scan speed: 600nm / min Sampling interval: 2nm
[0026] The metal compound-containing material used in the method for producing a coated structure of the present invention is characterized in that the particle diameter (D50) of the particles in the metal compound-containing material measured by dynamic light scattering is 3000 nm or less. The particle diameter (D50) of the particles in the metal compound-containing material used in the method for producing a coated structure of the present invention is preferably 3000 nm or less from the viewpoint of stability over time, more preferably 2000 nm or less, and may be 1000 nm or less, 500 nm or less, 400 nm or less, or 300 nm or less. On the other hand, the particle diameter (D50) is preferably 0.1 nm or more, more preferably 0.5 nm or more, even more preferably 0.7 nm or more, and particularly preferably 1 nm or more. Typically, the particle diameter (D50) is 0.6 nm or more and 200 nm or less.
[0027] Here, the dynamic light scattering method is a method in which a solution such as a suspension is irradiated with light such as a laser beam to measure the light scattering intensity from a group of particles undergoing Brownian motion, and the particle size and distribution are obtained from the temporal variation of the intensity. Specifically, the particle size distribution is evaluated using a zeta potential, particle size, and molecular weight measurement system (manufactured by Otsuka Electronics Co., Ltd.: ELSZ-2000ZS) in accordance with JIS Z 8828:2019 "Particle size analysis - dynamic light scattering method". In addition, if necessary, the measurement sample is diluted 1000 times with pure water, and the measurement sample is filtered with a filter with a pore size of 11 μm to remove dust and the like in the measurement sample immediately before measurement, and ultrasonic treatment is performed for 3 minutes with an ultrasonic cleaner (manufactured by As One Co., Ltd.: VS-100III). In addition, the liquid temperature of the measurement sample was adjusted to 25 °C. The particle size (D50) refers to the median diameter (D50), which is the particle size that shows the 50% cumulative value of the cumulative distribution curve.
[0028] The metal compound-containing material used in the method for producing a coated structure of the present invention is characterized by having a pH of 6.5 or more and 13.5 or less. The pH of the metal compound-containing material used in the method for producing a coated structure of the present invention is preferably 6.5 or more in terms of good solubility. The pH of the metal compound-containing material is more preferably 7.0 or more, even more preferably 7.5 or more, and particularly preferably 8.0 or more. The pH of the metal compound-containing material may be 8.5 or more, 9.0 or more, 9.5 or more, 10.0 or more, 10.5 or more, or 11.0 or more. On the other hand, the pH of the metal compound-containing material is preferably 13.5 or less, more preferably 13.0 or less, and even more preferably 12.5 or less.
[0029] Here, the pH of the metal compound-containing material used in the manufacturing method of the coated structure of the present invention is measured by immersing an electrode (HORIBA: Standard ToupH electrode 9615S-10D) of a pH meter (HORIBA: Glass electrode type hydrogen ion concentration indicator D-51) in the metal compound-containing material and confirming that the liquid temperature has stabilized at 25°C.
[0030] The metal compound-containing substance used in the method for producing a coated structure of the present invention may contain at least one selected from ammonia, an organic nitrogen compound, and aqueous hydrogen peroxide.
[0031] The metal compound-containing material used in the method for producing a coated structure of the present invention may contain at least one selected from ammonia, an organic nitrogen compound, and hydrogen peroxide, in addition to a compound of at least one metal element selected from Ti, Nb, Mo, Hf, Ta, W, and Zr. Furthermore, the "ammonia", "organic nitrogen compound", and "hydrogen peroxide" of the present invention include ionized forms of each of the "ammonia", "organic nitrogen compound", and "hydrogen peroxide" in the metal compound-containing material of the present invention.
[0032] Methods for measuring the concentration of ammonium ions in the contents include adding sodium hydroxide to the contents to separate the ammonia by distillation and quantifying the ammonium ion concentration using an ion meter, quantifying the N2 content in a gasified sample using a thermal conductivity meter, the Kjeldahl method, gas chromatography (GC), ion chromatography, and GC-MS (mass spectrometry).
[0033] On the other hand, examples of organic nitrogen compounds include aliphatic amines, aromatic amines, amino alcohols, amino acids, polyamines, quaternary ammonium compounds, guanidine compounds, and azole compounds.
[0034] Examples of aliphatic amines include methylamine, dimethylamine, trimethylamine, ethylamine, methylethylamine, diethylamine, triethylamine, methyldiethylamine, dimethylethylamine, n-propylamine, di-n-propylamine, tri-n-propylamine, isopropylamine, diisopropylamine, triisopropylamine, n-butylamine, di-n-butylamine, tri-n-butylamine, isobutylamine, diisobutylamine, triisobutylamine, tert-butylamine, n-pentamine, n-hexylamine, cyclohexylamine, piperidine, and the like.
[0035] Examples of aromatic amines include aniline, phenylenediamine, and diaminotoluene. Examples of amino alcohols include methanolamine, ethanolamine, propanolamine, butanolamine, pentanolamine, dimethanolamine, diethanolamine, trimethanolamine, methylmethanolamine, methylethanolamine, methylpropanolamine, methylbutanolamine, ethylmethanolamine, ethylethanolamine, ethylpropanolamine, dimethylmethanolamine, dimethylethanolamine, dimethylpropanolamine, methyldimethanolamine, methyldiethanolamine, diethylmethanolamine, trishydroxymethylaminomethane, bis(2-hydroxyethyl)aminotris(hydroxymethyl)methane, and aminophenol. Examples of amino acids include alanine, arginine, aspartic acid, and EDTA. Examples of polyamines include polyamines and polyetheramines.
[0036] Examples of quaternary ammonium include alkylimidazolium, pyridinium, pyrrolidium, tetraalkylammonium, etc. Specific examples of alkylimidazolium include 1-methyl-3-methylimidazolium, 1-ethyl-3-methylimidazolium, 1-propyl-3-methylimidazolium, 1-butyl-3-methylimidazolium, 1-hexyl-3-methylimidazolium, 1-methyl-2,3-dimethylimidazolium, 1-ethyl-2,3-dimethylimidazolium, 1-propyl-2,3-dimethylimidazolium, 1-butyl-2,3-dimethylimidazolium, etc. Specific examples of pyridinium and pyrrolidium include N-butyl-pyridinium, N-ethyl-3-methyl-pyridinium, N-butyl-3-methyl-pyridinium, N-hexyl-4-(dimethylamino)-pyridinium, N-methyl-1-methylpyrrolidinium, and N-butyl-1-methylpyrrolidinium. Specific examples of tetraalkylammonium include tetramethylammonium, tetraethylammonium, tetrabutylammonium, and ethyl-dimethyl-propylammonium. Examples of anions that form salts with the above-mentioned cations include OH, - , Cl - , Br - , I - , BF4 - , HSO4 - etc.
[0037] Examples of the guanidine compound include guanidine, diphenylguanidine, and ditolylguanidine. Examples of the azole compound include imidazole compounds and triazole compounds. Specific examples of the imidazole compound include imidazole, 2-methylimidazole, and 2-ethyl-4-methylimidazole. Specific examples of the triazole compound include 1,2,4-triazole, 1,2,4-triazole-3-methyl carboxylate, and 1,2,3-benzotriazole.
[0038] Methods for measuring the concentration of organic nitrogen compounds present in the material include gas chromatography (GC), liquid chromatography (LC), mass spectrometry (MS), gas chromatography-mass spectrometry (GC-MS), and liquid chromatography-mass spectrometry (LC-MS), and a method for quantifying the N2 content in the gasified sample using a thermal conductivity meter may also be used in combination.
[0039] Furthermore, the quantitative analysis of hydrogen peroxide present in the content is carried out by measuring the absorbance of the content at a wavelength of 410 nm using a spectrophotometer (U-2900 manufactured by Hitachi, Ltd.) to quantify the amount of hydrogen peroxide present in the content.
[0040] In the step of applying or immersing the substrate in a material containing a metal compound in the method for producing a coated structure of the present invention, the substrate is applied with or immersed in a material containing a metal compound.
[0041] Specific methods for applying the metal compound-containing material onto the substrate include spraying, inkjet, dispenser, nozzle coating, slit coating, die coating, roll coating, spin coating, blade coating, knife coating, wire bar coating, screen printing, brush coating, and the like.
[0042] The method of impregnating the substrate with the metal compound-containing material involves impregnating the substrate with the metal compound-containing material by immersing the substrate in a container filled with the metal compound-containing material. The immersion time in this step is preferably 0.1 to 1 hour, more preferably 0.2 to 0.9 hours. This step may be performed at room temperature, or may be heated and then cooled to room temperature.
[0043] In addition, the immersion step in the method for producing a coated structure of the present invention is preferable in that immersing the substrate in a material containing a metal compound under reduced pressure or in a vacuum makes it easier for the substrate to be impregnated with the material containing a metal compound, thereby shortening the immersion time in the step.
[0044] Specifically, a container filled with the metal compound-containing material in which the substrate is immersed is placed in a pressure reducing device and placed under reduced pressure or vacuum, whereby the substrate is more easily impregnated with the metal compound-containing material.
[0045] The degree of vacuum in the pressure reducing device is preferably 0.05 MPa or less, more preferably 0.04 MPa or less, even more preferably 0.03 MPa or less, and particularly preferably 0.02 MPa or less. The immersion time in the immersion step under reduced pressure or vacuum is preferably 0.1 hour to 0.5 hours, and more preferably 0.2 hour to 0.4 hours.
[0046] Furthermore, when a metal composite coating is formed only on one surface of a substrate, for example, on the surface, only the surface of the substrate is immersed in the metal compound-containing material, whereas when a metal composite coating is formed on the entire peripheral surface of the substrate, the entire peripheral surface of the substrate is immersed in the metal compound-containing material.
[0047] Next, in the discharge process in the method for manufacturing a coated structure of the present invention, a discharge electrode is used to repeatedly discharge between the discharge electrode and a substrate coated or immersed in a material containing a metal compound, thereby forming a metal composite coating on the substrate.
[0048] Specifically, a substrate coated with or immersed in a material containing a metal compound is set on a metal plate. Next, when a voltage is applied between the discharge electrode and the substrate coated with or immersed in the material containing a metal compound, a discharge occurs between the discharge electrode and the substrate coated with or immersed in the material containing a metal compound, causing the electrode material of the discharge electrode to react with the metal element in the material containing a metal compound applied to or immersed in the substrate, and this reaction is repeated to form a metal composite coating on the substrate.
[0049] The power sources added to the discharge electrodes used in the discharge process are all AC power sources, and AC pulse discharge is used. AC pulse discharge is a pulse discharge method that repeats ON and OFF in accordance with the frequency, 60Hz in Western Japan and 50Hz in Eastern Japan. In order to equalize the power supply, a bridge circuit is used for stabilization, and a sine wave is created by Fourier transformation. Furthermore, the discharge generated from the discharge electrode becomes a spiral pipe-shaped discharge, which melts the elements of the discharge electrode, makes them exist in the spiral pipe, and moves to the base material to which a negative potential has been applied. Since the elements from the discharge electrode exist in the spiral pipe discharge, oxygen and nitrogen from the atmosphere can be blocked, and oxidation and nitridation can be prevented. In addition, a bandpass circuit in the differentiation circuit and integration circuit in the middle of the bridge circuit is also necessary for the spiral pipe discharge.
[0050] In the method for producing a coated structure of the present invention, the discharge electrode is a metal electrode. When the discharge electrode is a metal electrode, the metal element contained in the metal electrode reacts with the metal element in the metal compound-containing material applied to or immersed in the substrate to form a composite metal compound, and a metal composite coating is formed on the substrate.
[0051] The method for producing a coated structure of the present invention is characterized in that the discharge electrode is at least one selected from a Ti electrode, a Nb electrode, a Mo electrode, a Hf electrode, a Ta electrode, a W electrode, and a Zr electrode. When the discharge electrode is at least one selected from a Ti electrode, a Nb electrode, a Mo electrode, a Hf electrode, a Ta electrode, a W electrode, and a Zr electrode, the at least one metal element selected as the discharge electrode reacts with a metal element in the metal compound-containing material applied to or immersed in the substrate to form a composite metal compound, and a metal composite coating is formed on the substrate.
[0052] In the method for producing a coated structure of the present invention, the discharge electrode is a carbon electrode. When the discharge electrode is a carbon electrode, the carbon contained in the carbon electrode reacts with the metal element in the metal compound-containing material applied to or immersed in the substrate to form a metal carbide, and a metal-carbon composite coating is formed on the substrate.
[0053] In the method for producing a coated structure of the present invention, it is preferable that AC power is supplied to the discharge electrode. By supplying AC power to the discharge electrode, plasma discharge occurs between the discharge electrode and the substrate coated with or immersed in the metal compound-containing material, which is preferable in that it is an electromagnetic pulse. On the other hand, when DC power is supplied to the discharge electrode, no electromagnetic pulse is generated, which is inconvenient.
[0054] In addition, in the method for producing a coated structure of the present invention, the voltage applied to the discharge electrode is preferably less than 4 kV in that it is a differential pulse. The voltage applied to the discharge electrode is more preferably 3.6 kV or less, even more preferably 3 kV or less, particularly preferably 2 kV or less, more particularly preferably 1 kV or less, even more particularly preferably 300 V or less, also particularly preferably 200 V or less, and most preferably 150 V or less. On the other hand, if the voltage applied to the discharge electrode is 4 kV or more, it does not become a differential pulse, which is problematic.
[0055] Furthermore, in the method for producing a coated structure of the present invention, when the substrate is a metal-based substrate, repeated discharges are generated between the discharge electrode and the substrate coated with or immersed in a metal compound-containing material, and in addition to the electrode material of the discharge electrode reacting with the metal elements in the metal compound-containing material coated on or immersed in the substrate, the metal compound-containing material also reacts with the metal elements present on the coating surface of the metal-based substrate to which the metal compound-containing material is coated, thereby forming a composite metal compound, and a metal composite coating can be formed on the substrate.
[0056] Here, when the discharge electrode is a metal electrode and the substrate is a metal-based substrate, a metal compound is formed by reacting with a metal element of the electrode material of the discharge electrode, a metal element in the metal compound-containing material applied to or immersed in the substrate, and a metal element present on the coating surface of the metal-based substrate to which the metal compound-containing material is applied, and a metal composite coating can be formed on the substrate.
[0057] Furthermore, when the discharge electrode is a carbon electrode and the substrate is a metal-based substrate, the carbon of the electrode material of the discharge electrode, the metal element in the metal compound-containing material applied to or immersed in the substrate, and the metal element present on the coating surface of the metal-based substrate to which the metal compound-containing material is applied react with each other to form a metal compound, and a metal composite coating can be formed on the substrate.
[0058] Furthermore, in the method for producing a coated structure of the present invention, when the substrate is a carbon-based substrate, repeated discharges are generated between the discharge electrode and the substrate coated with or immersed in a metal compound-containing material, whereby a metal compound is formed by reacting the electrode material of the discharge electrode with the metal element in the metal compound-containing material coated on or immersed in the substrate, as well as with carbon present on the coating surface of the carbon-based substrate coated with the metal compound-containing material, thereby forming a metal compound and forming a metal composite coating on the substrate.
[0059] Here, when the discharge electrode is a metal electrode and the substrate is a carbon-based substrate, a metal element of the electrode material of the discharge electrode, a metal element in the metal compound-containing material applied to or immersed in the substrate, and carbon present on the coating surface of the carbon-based substrate to which the metal compound-containing material is applied react with each other to form a composite metal compound, and a metal composite coating can be formed on the substrate.
[0060] When the discharge electrode is a carbon electrode and the substrate is a carbon-based substrate, the carbon of the electrode material of the discharge electrode, the metal element in the metal compound-containing material applied to or immersed in the substrate, and the carbon present on the coating surface of the carbon-based substrate to which the metal compound-containing material is applied react with each other to form a metal compound, and a metal composite coating can be formed on the substrate.
[0061] In addition, the method for producing a coated structure of the present invention may further include a drying step between the step of applying or immersing the substrate in the metal compound-containing material and the discharge step in the above-mentioned method for producing a coated structure of the present invention.
[0062] This is preferable in that the substrate coated or immersed in the metal compound-containing material is placed in a static furnace and dried at a drying temperature of 100° C. for 1 hour, which makes it possible to remove excess impurities such as moisture.
[0063] The drying temperature in the drying step is more preferably 110°C or higher and 400°C or lower, further preferably 120°C or higher and 300°C or lower, and particularly preferably 130°C or higher and 200°C or lower.
[0064] The drying time in the drying step is preferably from 0.2 hours to 3 hours, more preferably from 0.3 hours to 2 hours, and even more preferably from 0.4 hours to 1 hour.
[0065] By the above-mentioned method for producing a coated structure of the present invention, a coated structure having a metal composite coating formed on a substrate can be produced.
[0066] The metal composite coating formed on the substrate produced by the above-mentioned method for producing a coated structure of the present invention can be confirmed to be a metal compound from the peaks in the X-ray diffraction pattern obtained by X-ray diffraction measurement according to the following X-ray diffraction measurement conditions and X-ray diffraction analysis conditions.
[0067] =X-ray diffraction measurement conditions= Equipment: MiniFlexII (Rigaku Corporation) Measurement range (2θ): 5~90° Sampling width: 0.02° Scan speed: 2.0° / min ·X-ray: CuKα ray Voltage: 30kV ·Current: 15mA Divergence slit: 1.25° Scattering slit: 1.25° Receiving slit: 0.3 mm
[0068] =X-ray diffraction analysis conditions= Use Rigaku's data analysis software PDXL2. · Smooth the peaks with b-spline to clarify the peak tops.
[0069] Furthermore, if the thickness of the metal composite coating formed on the substrate manufactured by the method for manufacturing a coated structure of the present invention is 300 nm or less, this is preferable in that cracks in the film and peeling of the film itself are unlikely to occur. The thickness of the metal composite coating may be 100 nm or less. This is because if cracks occur in the metal composite coating, the substrate is oxidized and is likely to be released as an oxide, and the elements in the substrate are likely to decrease. On the other hand, if the thickness of the metal composite coating is 1 nm or more, this is preferable in that the substrate can be sufficiently protected. The thickness of the metal composite coating may be 10 nm or more.
[0070] The coated structure of the present invention is a coated structure having a metal-carbon composite coating on a substrate, and is characterized in that the metal-carbon composite coating has a D band / G band peak area ratio of 0.46 or more and 3.5 or less in Raman spectroscopy. The coated structure of the present invention has a metal-carbon composite coating on a substrate. When the metal-carbon composite coating has a D band / G band peak area ratio of 0.5 to 3.5 in Raman spectroscopy, the carbon structure is sp 3 This is preferable in that the structure is similar to that of the above-mentioned structure and the corrosion resistance is improved. The D band / G band peak area ratio is more preferably 1 or more and 3 or less, further preferably 1.5 or more and 2.7 or less, and particularly preferably 2.1 or more and 2.5 or less.
[0071] Here, Raman spectroscopy is a spectroscopic method for evaluating the chemical structure and bonding state of carbon materials. In the Raman spectrum of carbon materials, the peak at 1300 cm is usually observed. -1 ~1400cm -1 , and 1550 cm -1 ~1650cm -1 Highly crystalline graphite has a peak at 1550 cm -1 ~1650cm -1A single peak is observed at 1300 cm, which is called the "G band". On the other hand, as the crystallinity decreases (the number of crystal structure defects increases), -1 ~1400cm -1 A peak appears at 2400 cm, and this peak is called the "D band". The D band / G band peak area ratio is an index of the amount of defects in the crystal structure of the carbon material. The smaller the D band / G band peak area ratio, the fewer the amount of defects in the crystal structure of the carbon material. Carbon materials with fewer defects in the crystal structure have a peak at 2400 cm. -1 ~2800cm -1 A peak is also detected at 2D band, and this peak is called the "2D band". The D band / G band peak intensity ratio is sometimes called the R value.
[0072] The metal-carbon composite coating formed on the substrate can be confirmed to be a metal carbide from the peak (half width) of the Raman spectrum obtained by measuring the metal-carbon composite coating under the following Raman spectroscopy measurement conditions and Raman spectroscopy measurement conditions.
[0073] = Raman spectroscopy measurement conditions = Equipment: Invia Qontor (manufactured by Renishaw Ltd.) ·Light source: 532nm (RL532-08 150mW) Objective lens: 20x Grating: 1800mm / L Irradiation time: 5 to 10 seconds Number of times: 1 Slit width: 65μm Laser power: 1% ·Using Livetrac function 20x20 square map measurement (10μm intervals in both X and Y directions)
[0074] = Raman spectroscopy analysis conditions = The Raman spectrum obtained under the above-mentioned Raman spectroscopy measurement conditions was subjected to baseline correction (intelligence polynomial: degree 6) and average spectrum processing in WiRE5.5 manufactured by Renishaw Ltd., and the peak at 1550 cm -1 ~1650cm -1 Normalization is then performed so that the maximum value in the normalized spectrum is 1. Next, using Igor Pro ver. 8.04 manufactured by WaveMetrics, multipeak Fitting 2 is applied to the normalized spectrum, and the initial peak is set with reference to the description in Table 1 in Chapter 8, Section 4 of Raman Spectroscopic Data Analysis Case Studies (Technical Information Association, Inc.). The peak adopts a Gaussian or Lorentzian distribution. Then, fitting is repeatedly performed so that the χ-square, which represents the difference between the actual peak value and the fitting value, becomes as small as possible, and if the χ-square converges beyond 1.0, a new peak is set and fitting is repeated until the χ-square becomes less than 1.0.
[0075] Each peak obtained by the above-mentioned procedure is classified into D band and G band based on the peak position, the sum of the peak areas of each band is calculated, and the sum of the D band peak areas divided by the sum of the G band peak areas is defined as the D band / G band peak area ratio.
[0076] Furthermore, in the coated structure of the present invention, if the thickness of the metal-carbon composite coating formed on the substrate is 300 nm or less, it is preferable since cracks in the coating and peeling of the coating itself are unlikely to occur.
[0077] In this specification, when "X to Y" (X and Y are any numbers) is expressed, unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as "preferably greater than X" or "preferably smaller than Y". In addition, when "X or more" (X is any number) or "Y or less" (Y is any number), it also includes the meaning of "preferably greater than X" or "preferably less than Y". Effect of the Invention
[0078] The method for producing a coated structure of the present invention can form a stable metal composite coating at low temperatures by a discharge method, and can produce a coated structure having a uniform metal composite coating on the substrate while reducing the thermal history of the substrate. [Brief description of the drawings]
[0079] [Figure 1] Graph (a) shows the measurement results of a heat resistance test (SUS) of the coated structure of Example 2, and graph (b) shows the measurement results of a heat resistance test (SUS) of the metal-based substrate of Comparative Example 2. BEST MODE FOR CARRYING OUT THEINVENTION
[0080] The coated structure according to the embodiment of the present invention will be further described below with reference to the following examples, although the present invention is not limited to these examples.
[0081] Example 1 The tantalic acid compound dispersion was applied to the entire surface of a carbon-based substrate (length x width x thickness: 50 mm x 50 mm x 5 mm) using a brush. Next, the carbon-based substrate coated with the tantalic acid compound dispersion was placed in an electric furnace and dried for 10 minutes in an electric furnace heated to 110°C. Thereafter, the carbon-based substrate coated with the tantalic acid compound dispersion was set on a metal plate. Then, when a voltage was applied between the carbon electrode, which is a discharge electrode, and the carbon-based substrate coated with the tantalic acid compound dispersion, a discharge was generated between the carbon electrode and the carbon-based substrate coated with the tantalic acid compound dispersion, and carbon, which is the electrode material of the carbon electrode, reacted with tantalum in the tantalic acid compound dispersion applied to the substrate to form a tantalum compound. By repeating this process, a tantalum-carbon composite coating was formed on the substrate, and a coating structure according to Example 1 was obtained.
[0082] The tantalic acid compound dispersion liquid used in Example 1 was obtained as follows.
[0083] 137.9 g of tantalum hydroxide (Ta2O5 concentration 66 mass%) manufactured by Mitsui Mining & Smelting Co., Ltd. was dissolved in 120 g of a 55 mass% aqueous hydrofluoric acid solution, and 849 mL of ion-exchanged water was added to obtain an aqueous tantalum fluoride solution (Ta2O5 concentration 8.2 mass%).
[0084] 27.5 g of hydrogen peroxide solution (H2O2 concentration 35 mass %) was added to 1,000 g of this tantalum fluoride aqueous solution (H2O2 / Ta molar ratio = 0.76) and stirred for 5 minutes to obtain an aqueous tantalum compound solution.
[0085] 1,000 g of this tantalum compound aqueous solution was added to 6.82 L of ammonia water (NH3 concentration 25 mass %) in less than 10 minutes (NH3 / Ta molar ratio = 245, NH3 / HF molar ratio = 30.7) to obtain a reaction liquid (pH 11). This reaction liquid was a slurry of tantalic acid compound hydrate, in other words, a slurry of tantalum-containing precipitate.
[0086] Next, the reaction solution was decanted using a centrifuge and washed until the amount of liberated fluoride ions was 100 mg / L or less, to obtain a tantalum-containing precipitate from which the fluoride ions had been removed, using aqueous ammonia as the washing liquid.
[0087] Furthermore, the tantalum-containing precipitate from which the fluoride ions had been removed was diluted with pure water to obtain a tantalum-containing precipitate slurry. A portion of this tantalum-containing precipitate slurry was dried at 110°C for 24 hours and then fired at 1,000°C for 4 hours to produce Ta2O5, and the Ta2O5 concentration in the tantalum-containing precipitate slurry was calculated from its weight.
[0088] Then, the tantalum-containing precipitate slurry diluted with pure water, 5 mass% dimethylamine as an organic nitrogen compound, and pure water were mixed so that the tantalum concentration of the final mixture was 5 mass% in terms of Ta2O5 and the weight ratio of Ta2O5 / organic nitrogen compound was 1.0, thereby obtaining the tantalic acid compound dispersion liquid used in Example 1. The pH of the tantalic acid compound dispersion liquid used in Example 1 was 12.0.
[0089] On the other hand, an extrusion-molded carbon-based substrate was used as the carbon-based substrate in Example 1. However, the carbon-based substrate is not limited to extrusion molding.
[0090] Example 2 The entire surface of a metal-based substrate (SUS310) (length x width x thickness: 250 mm x 250 mm x 0.5 mm) was coated with the tantalic acid compound dispersion liquid using a brush. Next, the carbon-based substrate coated with the tantalic acid compound dispersion liquid was placed in an electric furnace and dried for 10 minutes in an electric furnace heated to 110°C. Thereafter, the metal-based substrate coated with the tantalic acid compound dispersion liquid was set on a metal plate. Then, when a voltage was applied between the carbon electrode, which is a discharge electrode, and the metal-based substrate coated with the tantalic acid compound dispersion liquid, a discharge was generated between the carbon electrode and the metal-based substrate coated with the tantalic acid compound dispersion liquid, and the carbon, which is the electrode material of the carbon electrode, reacted with the tantalum in the tantalic acid compound dispersion liquid coated on the substrate to form a tantalum compound, and this was repeated to form a tantalum-carbon composite coating on the substrate, and a coating structure according to Example 2 was obtained.
[0091] The tantalic acid compound dispersion liquid used in Example 2 was the same as the tantalic acid compound dispersion liquid used in Example 1, and therefore a detailed description thereof will be omitted.
[0092] On the other hand, the metallic base material used in Example 2 was made of SUS310.
[0093] Example 3 In Example 3, a coating structure according to Example 3 was obtained by carrying out a manufacturing method similar to that of Example 2, except that a tantalum-containing precipitate slurry diluted with pure water, 5 mass% dimethylamine as an organic nitrogen compound, and pure water were mixed so that the tantalum concentration in the final mixture was 3 mass% in terms of Ta2O5.
[0094] Comparative Example 1 In Comparative Example 1, the surface of the carbon-based substrate used in Example 1 was processed by repeatedly discharging the surface using a discharge electrode made of a Ta electrode.
[0095] Comparative Example 2 Comparative Example 2 is a metal-based substrate, specifically, a SUS protective tube for a thermocouple sensor [K type] in a molten metal furnace.
[0096] (Reference example 1) Reference Example 1 was a tantalum carbide powder produced as follows.
[0097] 120 kg of tantalum oxide manufactured by Mitsui Mining & Smelting Co., Ltd. and 22 kg of carbon black were weighed out on a platform balance and mixed by stirring for 5 minutes in a vertical mixer to obtain a mixed powder.
[0098] This mixed powder was filled into a carbon container (2 kg / bottle), fed into a resistance heating hydrogen furnace at a rate of two bottles per three hours, and fired at a temperature of 1,700°C for 14 hours to perform primary carbonization, obtaining a primary carbide.
[0099] This primary carbide was filled into a carbon crucible (100 kg / piece), which was then placed in a high-frequency induction heating vacuum furnace and fired at 1,800°C for 5 hours to obtain a secondary carbide.
[0100] The secondary carbide was cooled to room temperature in the high-frequency induction heating vacuum furnace, removed from the carbon crucible, and coarsely crushed into lumps with a diameter of 2 cm or less using a jaw crusher.
[0101] After the coarse crushing, the coarsely crushed secondary carbide was finely crushed using a jet mill, which is an airflow type crusher. The jet mill used for fine crushing was set at a feed rate of 10 kg / hr and a wind speed of 2.5 m / min.
[0102] The finely pulverized secondary carbide was then classified using a vibrating sieve, and the undersize particles (fine particle side) were collected to obtain tantalum carbide powder according to Reference Example 1.
[0103] The following physical properties were measured and evaluation tests were carried out for the coated structures according to Examples 1 to 3, the carbon-based substrate according to Comparative Example 1, the metal-based substrate according to Comparative Example 2, and the tantalum carbide powder according to Reference Example 1. The measurement methods for the physical properties and the test methods for the evaluation tests are shown below, and the physical properties are shown in Table 1. The evaluation test results are shown in Table 2 and FIG.
[0104] <Elemental analysis> If necessary, the sample was appropriately diluted with dilute hydrochloric acid, and the weight fraction in metal equivalent was measured using ICP emission spectrometry (Agilent Technologies: AG-5110) in accordance with JIS K0116:2014.
[0105] Dynamic Light Scattering The particle size distribution of the metal compound-containing material used in Examples 1 to 3 was evaluated using a zeta potential, particle size, and molecular weight measurement system (manufactured by Otsuka Electronics Co., Ltd.: ELSZ-2000) in accordance with JIS Z 8828:2019 "Particle size analysis - dynamic light scattering method". In addition, in order to remove dust and the like in the solution to be measured immediately before the measurement, the content was filtered with a filter having a pore size of 2 μm, and ultrasonic treatment was performed for 3 minutes at 28 kHz using an ultrasonic cleaner (manufactured by AS ONE Co., Ltd.: VS-100III). The particle size (D50) refers to the median size (D50), which is the particle size showing the 50% cumulative value of the cumulative distribution curve.
[0106] <Light transmittance measurement> 4 ml of the metal compound-containing material used in Examples 1 to 3 was placed in a quartz cell with an optical path length of 5.0 mm, and the light transmittance of the metal compound-containing material used in Examples 1 to 3 in the wavelength range of 500 nm to 700 nm was measured using a spectrophotometer according to the light transmittance measurement conditions described above.
[0107] <Heat resistance test> The weights of the coated structure according to Example 1 and the carbon-based substrate according to Comparative Example 1 before the heat resistance test (hereinafter referred to as pre-test weight) were measured. Next, the coated structure according to Example 1 and the carbon-based substrate according to Comparative Example 1 were placed in a tubular furnace and fired in a 5 vol% O2-95 vol% N2 mixed gas atmosphere at a heating temperature of 700°C for a heating time of 90 minutes. The fired coated structure according to Example 1 and the carbon-based substrate according to Comparative Example 1 were removed from the tubular furnace and the weights after the heat resistance test (hereinafter referred to as post-test weight) were measured. Then, the weight change (attenuation rate) in the heat resistance test was calculated from the pre-test weight and the post-test weight for the coated structure according to Example 1 and the carbon-based substrate according to Comparative Example 1.
[0108] <Heat resistance test (SUS)> The coated structure according to Example 2 and the metal-based substrate according to Comparative Example 2 were subjected to the following heat resistance test (SUS) to evaluate their heat resistance. As a sample for the heat resistance test (SUS), the substrate of the coated structure according to Example 2 was a SUS protective tube (tube diameter×length×thickness: φ250 mm×300 mm×0.1 mm) for a thermocouple temperature sensor [K type] in a molten metal furnace. Then, a tantalum-carbon composite coating was formed on the substrate, and the substrate was used as the sample for the heat resistance test (SUS). On the other hand, the metal-based substrate according to Comparative Example 2 was a SUS protective tube on which no tantalum-carbon composite coating or the like was formed.
[0109] The weight of the heat resistance test (SUS) sample obtained in this way before the heat resistance test (SUS) (hereinafter referred to as the weight before test (SUS)) was measured. Next, the heat resistance test (SUS) sample was immersed in molten metal maintained at 1200°C, and the first time when the sensor indicated an abnormal temperature exceeding ±200°C for 5 consecutive minutes (1 plot / mm, 5 points) was determined as the endurance time.
[0110] Raman spectroscopy For the coated structures according to Examples 2 and 3, the carbon-based substrate according to Comparative Example 1, and the tantalum carbide powder according to Reference Example 1, the Raman spectra measured under the above-mentioned Raman spectroscopy measurement conditions showed a peak at 1300 cm -1 ~1400cm -1 , and 1550 cm -1 ~1650cm -1 A peak was observed at 1550 cm -1 ~1650cm -1 The single peak observed in the graphite structure is called the "G band" and corresponds to a highly crystalline graphite structure (sp 2 On the other hand, 1300cm -1 ~1400cm -1 The peak observed in the diamond structure (sp 3 The D band / G band peak area ratio calculated according to the above-mentioned Raman spectroscopy analysis conditions is derived from the sp 2 Structure and sp 3 The larger the D band / G band peak area ratio, the more sp 3 This indicates that the abundance ratio of the structure is high.
[0111] [Table 1]
[0112] [Table 2]
[0113] In the coated structures of Examples 1 to 3, a uniform metal composite coating was formed on the substrate by using a discharge electrode and repeatedly discharging between the discharge electrode and the substrate coated with or immersed in a material containing a metal compound.
[0114] The coated structure according to Example 1 had a decay rate of 0.7% or less in the heat resistance test, which means that no weight loss was observed in the substrate, and the metal composite coating formed on the substrate improved the heat resistance of the substrate. On the other hand, the carbon-based substrate according to Comparative Example 1 had a decay rate of 2.3% in the heat resistance test.
[0115] As shown in Fig. 1(a), the coating structure according to Example 2 had a durability time of 169 minutes in the heat resistance test (SUS), which indicates that the metal composite coating formed on the substrate improved the heat resistance of the substrate. On the other hand, as shown in Fig. 1(b), the metal substrate according to Comparative Example 2 had a durability time of 102 minutes in the heat resistance test (SUS).
[0116] The coated structures of Examples 2 and 3 had a D band / G band peak area ratio of 0.46 or more and 3.5 or less in Raman spectroscopy of the metal-carbon composite coating formed on the substrate, and therefore had excellent corrosion resistance against heating temperatures in the heat resistance test.
[0117] The inventions disclosed in this specification include, in addition to the configurations of each invention or embodiment, those that are specified by changing these partial configurations to other configurations disclosed in this specification, to the extent applicable, or those that are specified by adding other configurations disclosed in this specification to these configurations, or those that are specified as higher-level concepts by deleting these partial configurations to the extent that partial action and effects are obtained. [Industrial Applicability]
[0118] The method for producing a coated structure according to the present invention is suitable as a method for producing a coated structure because it can form a stable metal composite coating at low temperatures by the discharge method, reduce the thermal history of the substrate, and form a uniform metal composite coating on the substrate. Specifically, the method for producing a coated structure according to the present invention can form a stable metal composite coating at low temperatures by the discharge method, making it possible to reduce energy costs. In addition, the method for producing a coated structure according to the present invention can reduce waste by improving heat resistance and reactivity resistance and extending the life of the substrate, making it possible to reduce energy costs in disposing of waste. In addition, the coated structure according to the present invention can form a stable metal composite coating at low temperatures by the discharge method, reduce the thermal history of the substrate, and form a uniform metal composite coating on the substrate, making it suitable as a coated structure. Specifically, the coated structure according to the present invention has a uniform metal composite coating on the substrate, so that it can improve heat resistance and reactivity resistance and extend the life of the substrate, making it possible to reduce waste and reduce energy costs in disposing of waste. These aspects will lead to the sustainable management of natural resources and efficient benefits, as well as achieving decarbonization (carbon neutrality).
Claims
1. A method for producing a coated structure having a metal composite coating on a substrate, comprising the steps of: A step of applying or immersing a metal compound-containing material on the substrate; A discharge step of forming a metal composite coating on the substrate by repeatedly discharging between the discharge electrode and the substrate coated or immersed with the metal compound-containing material using a discharge electrode; A method for producing a coated structure, comprising the steps of:
2. 2. The method for producing a coated structure according to claim 1, wherein the metal compound-containing substance contains a compound of at least one metal element selected from the group consisting of Ti, Nb, Mo, Hf, Ta, W and Zr.
3. 2. The method for producing a coated structure according to claim 1, wherein the material containing a metal compound has a maximum light transmittance of 70% or more in a wavelength range of 500 nm to 700 nm.
4. 2. The method for producing a coated structure according to claim 1, wherein the metal compound-containing material contains particles whose particle diameter (D50) measured by dynamic light scattering is 3000 nm or less.
5. 5. The method for producing a coated structure according to claim 1, wherein the substrate is a metal substrate or a carbon substrate.
6. 5. The method for producing a coated structure according to claim 1, wherein the discharge electrode is a metal electrode.
7. 7. The method for producing a coated structure according to claim 6, wherein the discharge electrode is at least one selected from the group consisting of a Ti electrode, a Nb electrode, a Mo electrode, a Hf electrode, a Ta electrode, a W electrode and a Zr electrode.
8. 5. The method for producing a coated structure according to claim 1, wherein the discharge electrode is a carbon electrode.
9. 5. The method for producing a coated structure according to claim 1, wherein an AC power is supplied to the discharge electrode.
10. 7. The method for producing a coated structure according to claim 6, wherein a voltage applied to the discharge electrode is less than 4 kV.
11. 11. The method for producing a coated structure according to claim 10, wherein a voltage applied to the discharge electrodes is 300 V or less.
12. 5. The method for producing a coated structure according to claim 1, wherein the metal compound coating has a thickness of 300 nm or less.
13. A coating structure having a metal-carbon composite coating on a substrate, The metal-carbon composite coating has a D band / G band peak area ratio of 0.46 to 3.5 in Raman spectroscopy.
14. 14. The coated structure according to claim 13, wherein the substrate is a metal substrate.
Citation Information
Patent Citations
Method for modifying carbon surface layer
JP1996208358A